Brain volumetric deficits in MAPT mutation carriers: a multisite study. Issue 1 (28th November 2020) - Chu, Stephanie A.; Flagan, Taru M.; Staffaroni, Adam M.; Jiskoot, Lize C.; Deng, Jersey; Spina, Salvatore; Zhang, Liwen; Sturm, Virginia E.; Yokoyama, Jennifer S.; Seeley, William W.; Papma, Janne M.; Geschwind, Dan H.; et al.
Abstract: Objective: MAPT mutations typically cause behavioral variant frontotemporal dementia with or without parkinsonism. Previous studies have shown that symptomatic MAPT mutation carriers have frontotemporal atrophy, yet studies have shown mixed results as to whether presymptomatic carriers have low gray matter volumes. To elucidate whether presymptomatic carriers have lower structural brain volumes within regions atrophied during the symptomatic phase, we studied a large cohort of MAPT mutation carriers using a voxelwise approach. Methods: We studied 22 symptomatic carriers (age 54.7 ± 9.1, 13 female) and 43 presymptomatic carriers (age 39.2 ± 10.4, 21 female). Symptomatic carriers' clinical syndromes included: behavioral variant frontotemporal dementia (18), an amnestic dementia syndrome (2), Parkinson's disease (1), and mild cognitive impairment (1). We performed voxel‐based morphometry on T1 images and assessed brain volumetrics by clinical subgroup, age, and mutation subtype. Results: Symptomatic carriers showed gray matter atrophy in bilateral frontotemporal cortex, insula, and striatum, and white matter atrophy in bilateral corpus callosum and uncinate fasciculus. Approximately 20% of presymptomatic carriers had low gray matter volumes in bilateral hippocampus, amygdala, and lateral temporal cortex. Within these regions, low gray matter volumes emerged in a subset of presymptomatic carriers as early as their thirties. Low white matter volumes arose infrequently among presymptomatic carriers. Interpretation: A subset of presymptomatic MAPT mutation carriers showed low volumes in mesial temporal lobe, the region ubiquitously atrophied in all symptomatic carriers. With each decade of age, an increasing percentage of presymptomatic carriers showed low mesial temporal volume, suggestive of early neurodegeneration.